The Future of the Yuan: Measuring the "Power" of Renminbi (RMB) - Miswar, Syarifah Huswatun (Khwopa Journal, 2024)
Money is one of the most important “creatures” of the state. It has both soft and hard power at the same time. The power of a country can be seen from the strength of its currency exchange rate and its spread, and it is found that the use of Yuan has increased significantly, especially in trade between China and its trading partners. This is driven by various factors, such as the Chinese government’s policy to promote the internationalization of Yuan, the establishment of an offshore Yuan market in Hong Kong, and Yuan’s role in the Belt and Road Initiative. Although the Yuan is not yet a global reserve currency, this article concludes that the Yuan’s Power as Hard Power and Soft Power is increasing, and the Yuan has strong potential to play a greater role in the international monetary system in the future, supported by China’s economic growth and the government’s efforts to increase its use globally.